Urban Landuse Changes in Sri Lanka with Special Reference to Kaduwela Town from 1975 to 2016 - Ratnayake, R.M.K.; Ranaweera, D. K. D. A. (International Journal of Innovative Research & Development, 2017)
Attached

The study of land use/land cover changes is very important to have proper planning and utilization of natural resources and their management. Traditional methods for gathering demographic, censuses data and analysis of environmental situation are not adequate for multi complex environmental studies since many problems often presented in environmental issues and great complexity of handling the multidisciplinary data set. Therefore, it does require new technologies like satellite remote sensing and Geographical Information Systems. The objective of the study is to identify the changing pattern of land use in Kaduwela Municipal Council from 1970’s to 2016. Primary and secondary data are to be used for the analysis. The secondary data from the UDA, Survey Department and land sat 5 images in 1975, 1980, 1997 and 2016. The primary data was collect using field checking and discussion held with offices and residence. The Land use of the urban sprawl in Kaduwela Municipal Council is change very fast. Specially most of the land uses are residential, commercial and service infrastructure facilities. The paddy, marshy or inland cultivation lands (Homestead) are the alternative land for use of residential, commercial and other urban activates. In addition, the land price of the area is increase very rapidly and fragmentation is increase and the size of the land plots is very small.
Keywords: Land Use Changes, GIS, Remote Sensing, Temporal Pattern, Urbanization and suburbanization